Drug-induced liver injury Arzneimitteltoxische hepatopathie - Rosshart, Stephan Patrick; Spangenberg, Hans Christian (Arzneimitteltherapie, 2011)
Drug induced liver injury (DILI) has become a serious health issue. Generally, drug induced liver injuries can be classified as being intrinsic (predictable) or idiosyncratic (non-predictable), the latter type being by far the most common. The incidence rate of DILI is estimated at about 13.9 per 100.000 inhabitants. While further research is still needed to obtain a better understanding of the pathogenesis of the idiosyncratic DILI, a number of genetic and non-genetic risk factors have already been identified. However, since genetic risk factors do not allow a prediction of the patients' risk for DILI so far, the identification of non-genetic risk factors is essential in clinical practice. The clinical manifestation, histology and laboratory results of DILI can mimic almost any form of acute and chronic liver disease. Therefore, other liver diseases have to be excluded prior the diagnosis of DILI, however the key to a successful diagnosis is a thorough anamnesis. Though DILI is diagnosed per exclusionem, the experienced clinician should generally be able to choose the appropriate primary diagnostic method. Currently, methodologies to assess the causality between medication and drug induced liver injury are being optimized. RUCAM is presently the most widely-used method and can be regarded as state-of-the-art. Antibiotics, analgesic and NSAIDs are among those drugs that are most frequently related to drug induced liver injuries. In view of the fact that many patients turn to complementary and alternative medicine, herbal drugs, dietary supplements - such as weight loss and muscle building supplements - and other over-the-counter agents, the effects of these substances should also be considered as triggers and or causes of DILI. The prognosis of DILI is in general good, since in most cases a full recovery is achieved. However severe cases leading to liver transplantation or death can occur. Chronic liver disease as a consequence of DILI has been reported to occur in approximately 3-6% of patients with DILI. Total bilirubin and AST levels are the most reliable predictors for a severe course of the disease leading to a high mortality and transplantation rate. Identifying and discontinuing the causative agent is considered to be the most effective therapeutic measure. Glucocorticoids may be effective when systemic immunoreactions are detectable, however no studies have evaluated their effect on disease progression so far. In summary, the diagnosis und treatment of DILI remains a challenging problem for clinicians, researchers and the pharmaceutical industry.
CRIS-Team Scopus Importer:2022-12-14
Keywords: CIOMS/RUCAM scale; DILI; Drug-induced liver injury; Hepatotoxicity